Management accounting information practices in Vietnamese labor export enterprises: A firm size perspective - Linh, Nguyen Thi; Du, Tran Thi; Hoa, Nguyen Thi Quynh (Edelweiss Applied Science and Technology, 2025)
Management accounting information serves as a critical source of data for organizational control, while also providing a foundation for policy formulation and performance evaluation. The higher the reliability of such information, the more effective managerial decision-making is likely to be. Consequently, management accounting becomes an indispensable tool for managers, particularly in sectors characterized by intense competition and strong influences from both domestic and international political–social factors, such as labor export. A survey conducted with 197 Vietnamese labor export enterprises reveals that the implementation of management accounting remains inconsistent, reflecting disparities in development among different groups of firms. Commonly applied techniques include full costing, variable costing, production budgeting, cash budgeting, cost–volume–profit analysis, and profitability analysis by customer and market segments. While larger enterprises tend to adopt more advanced management accounting tools, smaller firms are constrained by limited financial resources, specialized personnel, and managerial awareness of the benefits associated with modern management accounting practices. The findings reaffirm the crucial role of management accounting in enhancing managerial effectiveness, controlling costs, and supporting strategic planning, particularly within the highly competitive context of the international labor market.